An environmental audit of the wastewater discharges at SJ, SPS, LS, and Miguel Buildings of De La Salle University-Manila. - Ang, Emeral Jaclyn C. (Animo Repository, 1999)
Reduction of pollutant emissions associated with research and educational activities is an important objective in line with making De La Salle University (DLSU) a model of sustainability. Research and educational institutions have unique waste management problems. Even though the volume of their wastes is minimal compared to typical industrial operations, the diversity of the wastes is considerable. Among the major contributors of wastes in DLSU-Manila are the chemistry laboratories which are known to utilize a large quantity of chemicals daily, some of which are found to be harmful to the environment. Through random sampling, samples were collected from the chemistry laboratories and from some of the discharge points around the university. Tests were conducted in order to characterize the wastes using the parameters chemical oxygen demand (COD), total suspended solids (TSS), and pH. Test results of the samples from the chemistry laboratories show that the laboratories effluents registered a high COD and TSS value, particularly laboratories which uses large amounts of organic chemicals. From the results of the samples from the sewers, SJ and SPS were identified as the discharge points that possess high COD and TSS values which are above the DENR standards. This may be attributed to the presence of the chemistry laboratories and canteen located in the respective buildings.